A comparative analysis on performances of flat plate photovoltaic/thermal collectors in view of operating media, structural designs, and climate conditions. (March 2020) - Pang, Wei; Cui, Yanan; Zhang, Qian; Wilson, Gregory.J.; Yan, Hui
Abstract: It is well known the efficiency of photovoltaic (PV) modules decreases with an increase in operating temperature. In this paper, we have investigated this phenomenon through classification of the flat plate photovoltaic/thermal (PV/T) collector into four configurations (air-type, water-type, nanofuid-type and bi-fluid-type), according to the media used for operation. Benefits of using the different operation media were assessed and an optimum for high overall efficiency of the PV/T collector was achieved. Considering different variation trends in electrical and thermal efficiency of the PV/T collector, the effects of operation media, structural designs and climatic conditions on performances of flat plate PV/T collectors were discussed in consideration of relevant literature reports. Results demonstrated that the overall efficiency of a water-type PV/T collector was greater than an air-type PV/T collector, benefitting from the higher specific heat capacity of water yet with a complex structure. The nanofluid-type PV/T collector presented a higher overall efficiency than the others, due to the high thermal conductivity of dispersing nanoparticles in a base fluid and the colloidal stability of the nanofluid. Furthermore, the glass cover (with or without), absorber structure and relative location between the absorber and the fluid influenced the overall performance of the PV/T collector. In addition, the primary climatic conditions to influence performance were solar radiation and environmental temperature, with a dependence on the geographical installation region. Future studies were considered through progression of advanced PV/T technologies, when the PV/T collector could be integrated with residential and public buildings. Highlights: Flat plate PV/T collectors were classified as four types by various operation media. Operation media, structural designs and climatic conditions were effected on PV/T collectors. The electrical and thermal efficiencies were compared related to different locations.